ASSESSING THE IMPACT OF INTERNSHIP, SELF-EFFICACY, AND CAREER GUIDANCE ON WORK READINESS IN VOCATIONAL SCHOOL STUDENTS - Ma'arif, Syamsul; Zulaihati, Sri; Swaramarinda, Darma Rika (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2025)
The background of this research is based on the low level of work readiness of vocational high school graduates as reflected in open unemployment data and the low percentage of graduates who work immediately after graduation. This study aims to determine the effect of Field Work Practice, Self-Efficacy, and Career Guidance on students' Work Readiness. The research method used is a quantitative approach with a sampling technique, namely proportional random sampling, with a sample size of 125 students. The data collection technique in this study used a questionnaire with a Likert Scale of 1-5. The data analysis technique in this study used descriptive statistics, classical assumption tests, and multiple regression analysis. The results of the analysis show that field work practice has a significant but negative effect on work readiness, while self-efficacy and career guidance have a positive and significant effect.These findings emphasize the need to review the Field Work Practice system which has a negative impact on students' work readiness, as well as the importance of strengthening self-efficacy and career guidance services as strategies to improve overall work readiness.